Regulation of calbindin D-28K by 1,25(OH)b2Db3 in MDBK cells. - Gagnon, AnneMarie. (University of Ottawa (Canada), 1996)
1,25-dihydroxyvitamin D$\sb3$ (1,25(OH)$\sb2\rm D\sb3$), the hormonally active form of vitamin D, mediates its effects, at least partially, via binding to its nuclear receptor, the vitamin D receptor (VDR) which then interacts with vitamin D-response elements in the promoter region of vitamin D-regulated genes. Our studies have focused on the regulation of calbindin D-28K, a vitamin D-dependent calcium-binding protein, in Madin-Darby bovine kidney (MDBK) cells. MDBK cells are renal epithelial cells which display distal tubular characteristics including the expression of calbindin D-28K and VDR. Consistent with data derived in primary cultures and in vivo models, we have characterized the dose- and time-dependence of calbindin D-28K regulation by 1,25(OH)$\sb2\rm D\sb3$, offering the first established in vitro model system for studying the molecular regulation of calbindin D-28K. Our data also emphasize the role of post-transcriptional mechanisms of regulation in calbindin D-28K induction by 1,25(OH)$\rm\sb2D\sb3$. The observation that protein kinase C (PKC) activators and inhibitors can modulate the expression of vitamin D-dependent proteins implicates this signalling pathway in 1,25(OH)$\rm\sb2D\sb3$ regulation. We have investigated the potential role of PKC in the regulation of calbindin D-28K in MDBK cells. Time course analysis with 1,25(OH)$\rm\sb2D\sb3$ and TPA, a well-characterized PKC modulator, suggests a temporal correlation between PKC activity and calbindin D-28K expression in MDBK cells. More precisely, both long term treatment with 1,25(OH)$\rm\sb2D\sb3$ and short term treatment with TPA induce PKC activity, PKC$\alpha$ immunoreactivity and calbindin D-28K expression. Long term treatment with TPA which down-regulates PKC activity and expression also causes a decrease in calbindin D-28K levels. The observation that phosphatase inhibitors blunt the down-regulating effect of TPA on calbindin D-28K expression further suggests a role for phosphorylation in this regulation. Amino acid sequence analysis of calbindin D-28K reveals the presence of five casein kinase II (CKII) and two PKC phosphorylation sites. In vitro phosphorylation assays demonstrate that PKC, and more precisely PKC$\alpha$, phosphorylates calbindin D-28K in a calcium- and phospholipid-dependent manner. In agreement with the amino acid sequence, the phosphorylated form of calbindin D-28K is detected with an anti-phosphothreonine antibody. CKII does not phosphorylate calbindin D-28K under our experiment conditions. Immunoprecipitation studies of radiolabeled MDBK cells further support the phosphorylation of calbindin D-28K. Both TPA and 1,25(OH)$\rm\sb2D\sb3$ treatments enhance the phosphorylation state of 28 kDa protein specifically immunoprecipitated in the presence of calbindin D-28K antibodies. These data have been compiled into a hypothetical model involving the phosphorylation of calbindin D-28K as a 1,25(OH)$\rm\sb2D\sb3$ regulatory step. Our results strongly implicate the PKC signalling pathway in calbindin D-28K regulation.
Keywords: Biology, Molecular.